2013
DOI: 10.2147/opth.s44523
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ocular perfusion pressure and ocular pulse amplitude in glaucoma, ocular hypertension, and normal eyes

Abstract: BackgroundThe purpose of this study was to investigate the correlation between ocular perfusion pressure and ocular pulse amplitude in glaucoma, ocular hypertension, and normal eyes.MethodsNinety eyes from 90 patients were included. Thirty patients had been recently diagnosed with glaucoma and had no previous history of treatment for ocular hypotension, 30 had elevated intraocular pressure (IOP) without evidence of glaucoma, and 30 had normal IOP (<21 mmHg) with no detectable glaucomatous damage. Goldmann appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…For instance, a study by Klein BE et al demonstrated that BMI is positively associated with IOP, suggesting that obesity may contribute to elevated eye pressure, potentially due to increased episcleral venous pressure and resistance to aqueous outflow [13] . Similarly, the relationship between height and IOP, as highlighted in our results, is supported by findings from other research, such as the work by Hepsen IF et al, which posited that taller individuals tend to have deeper anterior chambers and, consequently, different IOP dynamics [14] . Age as a correlate of IOP further enriches the discussion.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a study by Klein BE et al demonstrated that BMI is positively associated with IOP, suggesting that obesity may contribute to elevated eye pressure, potentially due to increased episcleral venous pressure and resistance to aqueous outflow [13] . Similarly, the relationship between height and IOP, as highlighted in our results, is supported by findings from other research, such as the work by Hepsen IF et al, which posited that taller individuals tend to have deeper anterior chambers and, consequently, different IOP dynamics [14] . Age as a correlate of IOP further enriches the discussion.…”
Section: Discussionsupporting
confidence: 92%
“…Kynigopoulos et al reported that low OPA was related to functional and structural damage in primary open angle glaucoma [21]. In contrast, the results of a study by Figueiredo et al, showed significantly lower mean OPA in the control group than in the patients with glaucoma or ocular hypertension [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Ocular perfusion pressure (OPP) is defined as arterial blood pressure minus IOP. 15 Many factors, such as vascular resistance, blood oxygen levels and hypothermia, might affect OPP. 16,17 It was shown that retinal blood flow remains unchanged despite large alterations in OPP 18,19 .…”
Section: Discussionmentioning
confidence: 99%